battery

CN122930841APending Publication Date: 2026-10-16TOYOTA JIDOSHA KK
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610379337.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2025-04-04
Filing Date
2026-03-26
Publication Date
2026-10-16

AI Technical Summary

Benefits of technology

[0023]根据本公开,可以提供能够提高电池的快速充电性能的电池。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122930841A_ABST
    Figure CN122930841A_ABST
Patent Text Reader

Abstract

Provided is a battery capable of improving the rapid charging performance of the battery. A battery sequentially includes a positive electrode, an electrolyte layer, and a negative electrode, the positive electrode sequentially includes a positive electrode layer and a positive electrode current collector from the electrolyte layer side, the positive electrode layer includes lithium manganese iron phosphate (LMFP) and lithium iron phosphate (LFP) having an olivine structure as a positive electrode active material, the upper limit voltage of the battery is less than 4.45 V, the positive electrode layer is bisected in a direction perpendicular to the thickness direction, the electrolyte layer side is taken as a first positive electrode layer, and the positive electrode current collector side is taken as a second positive electrode layer, and the content of lithium iron phosphate in the first positive electrode layer is greater than that in the second positive electrode layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure relates to batteries. Background Technology

[0002] Various technologies have been proposed for the batteries disclosed in Patent Documents 1 and 2.

[0003] Existing technical documents

[0004] Patent Document 1: Japanese Patent Publication No. 2024-519752

[0005] Patent Document 2: Japanese Patent No. 6132180 Summary of the Invention

[0006] Previously, to improve battery energy density, the use of lithium manganese iron phosphate (LFP) in addition to lithium iron phosphate was investigated. However, since the reaction potential of Mn is approximately 4.1V, close to the upper limit voltage of typical batteries (4.2-4.3V), the upper limit voltage of the battery is reached quickly during fast charging. While simply increasing the upper limit voltage from, for example, 4.3V to 4.4V improves the battery's fast charging performance, it also introduces a trade-off, such as frequent electrolyte decomposition.

[0007] This disclosure was made in view of the above-mentioned circumstances, and its main purpose is to provide a battery that can improve the fast charging performance of the battery.

[0008] That is, this disclosure includes the following scheme.

[0009] <1>

[0010] A battery comprising, in sequence, a positive electrode, an electrolyte layer, and a negative electrode.

[0011] The positive electrode has a positive electrode layer and a positive electrode current collector sequentially from the electrolyte layer side.

[0012] The positive electrode layer contains lithium manganese iron phosphate (LMFP) and lithium iron phosphate (LFP) with an olivine structure as positive electrode active materials.

[0013] The upper limit voltage of the battery is less than 4.45V.

[0014] When the positive electrode layer is divided into two equal parts in a direction perpendicular to the thickness direction, with the electrolyte layer side as the first positive electrode layer and the positive current collector side as the second positive electrode layer, the lithium iron phosphate content of the first positive electrode layer is greater than that of the second positive electrode layer.

[0015] <2>

[0016] according to <1> In the battery, the proportion of lithium iron phosphate in the second positive electrode layer on the positive electrode current collector side, relative to the total of lithium manganese iron phosphate and lithium iron phosphate, is less than 10% by mass.

[0017] <3>

[0018] according to <1> or <2> In the battery described above, the ratio of Mn to the total of Mn and Fe in the lithium manganese iron phosphate, Mn / (Mn+Fe), is 50 mol% or more.

[0019] <4>

[0020] according to <1> ~ <3> The battery described in any one of the following statements has an upper limit voltage of 4.40V or less.

[0021] <5>

[0022] according to <1> ~ <4> In any one of the batteries, the proportion of lithium iron phosphate in the first positive electrode layer on the electrolyte layer side, relative to the total proportion of lithium manganese iron phosphate and lithium iron phosphate, is 20% or more by mass.

[0023] According to this disclosure, a battery capable of improving the fast charging performance of a battery can be provided. Attached Figure Description

[0024] Figure 1 This is a cross-sectional schematic diagram illustrating an example of the structure of the battery disclosed herein.

[0025] Explanation of reference numerals in the attached figures

[0026] 10 …Positive current collector

[0027] 20 … Positive electrode layer

[0028] 21 …First Positive Electrode Layer

[0029] 22 …Second Positive Electrode Layer

[0030] 30 …electrolyte layer

[0031] 40 … Negative electrode layer

[0032] 50 … Negative current collector

[0033] 60 …LFP

[0034] 100 … batteries Detailed Implementation

[0035] The following describes embodiments of this disclosure. Furthermore, matters necessary for the implementation of this disclosure, other than those specifically mentioned in this specification (e.g., the general structure and manufacturing process of a battery not characteristic of this disclosure), can be grasped by those skilled in the art based on existing technology. This disclosure can be implemented based on the content disclosed in this specification and common technical knowledge in the art.

[0036] In addition, the dimensional relationships (length, width, thickness, etc.) in the diagram do not reflect the actual dimensional relationships.

[0037] Unless otherwise specified, elements described in the "singular form" may also include plural forms. For example, a particle may sometimes represent multiple particles (a swarm of particles).

[0038] In this disclosure, an example of a method for calculating the average particle size is as follows. First, in a transmission electron microscope (TEM) image or a scanning electron microscope (SEM) image at an appropriate magnification (e.g., 50,000 to 1,000,000 times), the particle size at which the particle is considered spherical is calculated for a given particle. This particle size calculation based on TEM or SEM observations is performed on 2 to 300 particles of the same type, and the average value of these particles is taken as the average particle size.

[0039] This disclosure provides a battery that sequentially comprises a positive electrode, an electrolyte layer, and a negative electrode.

[0040] The positive electrode has a positive electrode layer and a positive electrode current collector sequentially from the electrolyte layer side.

[0041] The positive electrode layer contains lithium manganese iron phosphate (LMFP) and lithium iron phosphate (LFP) with an olivine structure as positive electrode active materials.

[0042] The upper limit voltage of the battery is less than 4.45V.

[0043] When the positive electrode layer is divided into two equal parts in a direction perpendicular to the thickness direction, with the electrolyte layer side as the first positive electrode layer and the positive current collector side as the second positive electrode layer, the lithium iron phosphate content of the first positive electrode layer is greater than that of the second positive electrode layer.

[0044] In this disclosure, when the positive electrode layer, which is mainly composed of lithium manganese iron phosphate (LMFP) with an olivine structure, is divided into an electrolyte layer side and a positive electrode current collector side, the electrolyte layer side contains more lithium iron phosphate (LFP) with the same olivine structure compared to the positive electrode current collector side. By distributing more LFP with a low operating potential on the electrolyte layer side of the positive electrode layer, which preferentially reacts during fast charging of the battery, it is possible to suppress the voltage rise of the battery during fast charging, thereby providing a battery that suppresses electrolyte decomposition, is low-cost, and has high fast-charging performance.

[0045] Figure 1 This is a cross-sectional schematic diagram illustrating an example of the structure of the battery disclosed herein. For example... Figure 1 As shown, the battery 100 of this disclosure sequentially comprises a positive current collector 10, a positive electrode layer 20, an electrolyte layer 30, a negative electrode layer 40, and a negative current collector 50.

[0046] In the battery 100, when the positive electrode layer 20 is bisected in a direction perpendicular to the thickness direction, with the electrolyte layer 30 side designated as the first positive electrode layer 21 and the positive current collector 10 side designated as the second positive electrode layer 22, the first positive electrode layer 21 contains LFP60, while the second positive electrode layer 22 does not contain LFP60. That is, the LFP60 content of the first positive electrode layer 21 is greater than that of the second positive electrode layer 22.

[0047] The battery disclosed herein comprises, in sequence, a positive electrode, an electrolyte layer, and a negative electrode.

[0048] The upper limit voltage of the battery is less than 4.45V, but it can also be below 4.40V, 4.35V, or 4.30V.

[0049] [positive electrode]

[0050] The positive electrode consists of a positive electrode layer and a positive current collector, starting from the electrolyte layer side.

[0051] The positive electrode layer can be disposed on one surface of the positive electrode current collector or on both surfaces of the positive electrode current collector.

[0052] The positive electrode layer contains positive electrode active material, and may also contain at least one of electrolyte, conductive material and binder as needed.

[0053] The positive electrode layer contains lithium manganese iron phosphate (LMFP) with an olivine structure (olivine-type crystal structure) and lithium iron phosphate (LFP) with an olivine structure as positive electrode active materials.

[0054] When the positive electrode layer is bisected in a direction perpendicular to the thickness direction, with the electrolyte layer side as the first positive electrode layer and the positive current collector side as the second positive electrode layer, the lithium iron phosphate (LFP) content of the first positive electrode layer is greater than that of the second positive electrode layer. As long as the LFP content of the first positive electrode layer is greater than that of the second positive electrode layer, the mass ratio of LFP in the first positive electrode layer to that in the second positive electrode layer is not particularly limited, and can be 100:0 to 51:49 mass%. As long as the first positive electrode layer on the electrolyte layer side contains LFP, the second positive electrode layer on the positive current collector side may not contain LFP. Furthermore, in this disclosure, even if the second positive electrode layer does not contain LFP, it is permissible for LFP to be unintentionally mixed into the second positive electrode layer as an impurity near the interface between the first and second positive electrode layers during their formation. The impurities contained in the second cathode layer can also be less than 0.01% by mass.

[0055] Since the first cathode layer and the second cathode layer are obtained by bisecting the cathode layer in a direction perpendicular to the thickness direction, the first cathode layer and the second cathode layer have the same thickness.

[0056] The cathode layer contains at least a first cathode layer and a second cathode layer.

[0057] Depending on the requirements, the positive electrode layer can also be divided into three equal parts in a direction perpendicular to the thickness direction, with a first positive electrode layer, a second positive electrode layer, and a third positive electrode layer sequentially from the electrolyte layer side. In this case, the first positive electrode layer on the electrolyte layer side has the highest LFP content, and the third positive electrode layer on the positive current collector side has the lowest LFP content. The thicknesses of the first, second, and third positive electrode layers are the same.

[0058] Depending on the requirements, the positive electrode layer can also be divided into four equal parts in a direction perpendicular to the thickness direction, sequentially having a first positive electrode layer, a second positive electrode layer, a third positive electrode layer, and a fourth positive electrode layer starting from the electrolyte layer side. In this case, the first positive electrode layer on the electrolyte layer side has the highest LFP content, and the second positive electrode layer has a lower LFP content than the first positive electrode layer, and the third positive electrode layer has a lower LFP content than the second positive electrode layer, while the fourth positive electrode layer on the positive current collector side has the lowest LFP content. The thicknesses of the first, second, third, and fourth positive electrode layers are the same.

[0059] The first, second, third, and fourth cathode layers are sometimes collectively referred to as cathode layers.

[0060] The lower limit of the ratio of lithium iron phosphate (LFP) to the total of lithium manganese iron phosphate (LMFP) and lithium iron phosphate (LFP) in the first positive electrode layer on the electrolyte layer side, LFP / (LMFP+LFP), can be more than 10% by mass or more than 20% by mass, and the upper limit can be less than 50% by mass or less than 30% by mass, taking into account energy density.

[0061] The ratio of lithium iron phosphate (LFP) to lithium manganese iron phosphate (LMFP) and lithium iron phosphate (LFP) in the second positive electrode layer on the positive current collector side, LFP / (LMFP+LFP), can be less than 10% by mass, less than 5% by mass, less than 1% by mass, less than 0.1% by mass, less than 0.01% by mass, or 0% by mass.

[0062] The lower limit of the ratio of lithium iron phosphate (LFP) to the total of lithium manganese iron phosphate (LMFP) and lithium iron phosphate (LFP) in the entire cathode layer, LFP / (LMFP+LFP), can be above 5% by mass or above 10% by mass. Considering energy density, the upper limit can be below 25% by mass or below 15% by mass.

[0063] The ratio of Mn to the total Mn and Fe in lithium manganese iron phosphate (LMFP), Mn / (Mn+Fe), can have a lower limit of 50 mol% or more and an upper limit of 90 mol% or less or 75 mol% or less.

[0064] The proportion of positive electrode active material in the positive electrode layer can be, for example, 20% by mass or more, 30% by mass or more, or 40% by mass or more. If the proportion of positive electrode active material is too low, sufficient energy density may not be obtained. On the other hand, the proportion of positive electrode active material in the positive electrode layer can be, for example, 95% by mass or less, 70% by mass or less, or 60% by mass or less. If the proportion of positive electrode active material is too high, the ionic conductivity and electronic conductivity in the positive electrode layer may decrease relatively.

[0065] Positive electrode active material can also be particles.

[0066] The average particle size of the positive electrode active material can be, for example, greater than 0.5 μm or greater than 1.0 μm. The average particle size of the positive electrode active material can be less than 100 μm or less than 30 μm.

[0067] As electrolytes, examples include solid electrolytes. Solid electrolytes can be inorganic solid electrolytes such as sulfide solid electrolytes, halide solid electrolytes, oxide solid electrolytes, and complex hydride solid electrolytes, or organic solid electrolytes such as gel electrolytes.

[0068] A sulfide solid electrolyte is an electrolyte containing the S element. The sulfide solid electrolyte usually contains at least the Li element and the S element. The sulfide solid electrolyte may further contain an M element (M is at least one of P, As, Sb, Si, Ge, Sn, B, Al, Ga and In). In addition, the sulfide solid electrolyte may also contain halogen elements such as F, Cl, Br and I.

[0069] The sulfide solid electrolyte may be a glass-based (amorphous-based) sulfide solid electrolyte, may be a glass-ceramic-based sulfide solid electrolyte, or may be a crystalline-based sulfide solid electrolyte. The sulfide solid electrolyte may also have a crystalline phase. Examples of the above crystalline phase include a Thio-LISICON type crystalline phase, a thio-LISICON type crystalline phase, a argyrodite type crystalline phase, and an LGPS type crystalline phase, etc.

[0070] The composition of the sulfide solid electrolyte is not particularly limited, and examples thereof include xLi2S·(1-x)P2S5 (0.5≤x<1) and yLiI·zLiBr·(100-y-z)(xLi2S·(1-x)P2S5) (0.5≤x<1, 0≤y≤30, 0≤z≤30), etc. Among these compositions, x may satisfy 0.7≤x≤0.8. In addition, as another example of the composition of the sulfide solid electrolyte, Li 7-x PS 6-x X x . X is at least one of F, Cl, Br and I, and x satisfies 0≤x<2. In addition, as another example of the composition of the sulfide solid electrolyte, Li 4-x Me 1-x P x S4 (0<x<1). Me is at least one of Al, Zn, In, Ge, Si, Sn, Sb, Ga and Bi. Examples of the sulfide solid electrolyte include LiI-LiBr-Li2S-P2S5, LiI-Li2S-P2S5, LiI-Li2S-P2O5 and LiI-Li3PO4-P2S5, etc.

[0071] Examples of the oxide solid electrolyte include substances having a garnet-type crystal structure, etc., and the garnet-type crystal structure has a Li element, a La element, an A element (A is at least one of Zr, Nb, Ta and Al) and an O element. The oxide solid electrolyte may be, for example, Li2O-B2O3-P2O5, Li2O-SiO2, Li2O-B2O3, Li 1.3 Al 0.3 Ti 0.7 (PO4)3, Li5La3Ta2O 12 , Li7La3Zr2O 12 , Li6BaLa2Ta2O12 Li 3.6 Si 0.6 P 0.4 O4, Li4SiO4, Li3PO4 and Li 3+x PO 4-x N x (1≤x≤3), etc.

[0072] Examples of halide solid electrolytes include solid electrolytes containing Li, D, and X (where D represents at least one of Ti, Al, and Y, and X represents F, Cl, or Br).

[0073] Gel electrolytes may also comprise an electrolyte and a polymeric material. The polymeric material may also form a polymeric matrix. For example, the polymeric material may also comprise at least one selected from polyvinylidene fluoride (PVdF), polyvinylidene fluoride-co-hexafluoropropylene (PVDF-HFP), polyacrylonitrile (PAN), PVdF-PAN, polyethylene oxide (PEO), polyethylene glycol (PEG), and their derivatives.

[0074] From an operational point of view, solid electrolytes can also be in particle form.

[0075] In addition, the average particle size of solid electrolytes is not particularly limited and can range from 1 nm to 100 μm.

[0076] The proportion of solid electrolyte in the positive electrode layer can be, for example, 1% by mass or more. If the proportion of solid electrolyte is too low, the ion conduction pathways in the positive electrode layer may be insufficient. On the other hand, the proportion of solid electrolyte in the positive electrode layer can be, for example, 60% by mass or less. If the proportion of solid electrolyte is too high, the proportion of positive electrode active material will be relatively low, and the energy density may decrease.

[0077] The positive electrode layer can also contain conductive materials. By adding conductive materials, the electronic conductivity of the positive electrode layer is improved. Examples of conductive materials include carbon-based conductive materials, metal particles, and conductive polymers. Examples of carbon-based conductive materials include particulate materials such as acetylene black (AB) and Ketjen black (KB), and fibrous materials such as vapor-grown carbon fibers (VGCF), carbon nanotubes (CNTs), and carbon nanofibers (CNFs).

[0078] The proportion of conductive material in the positive electrode layer can be, for example, 0.1% by mass or more. If the proportion of conductive material is too low, the electron conduction pathways in the positive electrode layer may be insufficient. On the other hand, the proportion of conductive material in the positive electrode layer can be, for example, 5% by mass or less. If the proportion of conductive material is too high, the proportion of positive electrode active material becomes relatively low, and the energy density may decrease.

[0079] The positive electrode layer may also contain an adhesive. Examples of adhesives include styrene-butadiene rubber (SBR), polyimide (PI), polyacrylic acid (PAA), acrylonitrile-butadiene rubber (NBR), butadiene rubber (BR), polyvinylidene fluoride (PVdF), polytetrafluoroethylene (PTFE), styrene-isoprene-styrene block copolymer (SIS), and ethylene-propylene-diene copolymer (EPDM).

[0080] The proportion of binder in the positive electrode layer can be, for example, 0.5% by mass or more. If the proportion of binder is too small, it may not be able to adequately reduce the increase in resistance caused by charging and discharging. On the other hand, the proportion of binder in the positive electrode layer can be, for example, 15% by mass or less. If the proportion of binder is too large, the proportion of positive electrode active material will be relatively small, and the energy density may be low.

[0081] The thickness of the positive electrode layer can be, for example, 0.1 μm or more and 1000 μm or less, 1 μm or more and 500 μm or less, or 30 μm or more and 100 μm or less.

[0082] There are no particular limitations on the manufacturing method of the positive electrode layer; for example, the following methods can be listed.

[0083] First, prepare olivine-type LFP as the first positive electrode active material and olivine-type LMFP as the second positive electrode active material.

[0084] The second positive electrode active material, the above-mentioned conductive material, the above-mentioned binder and solvent are mixed to obtain a slurry for the second positive electrode layer, and the above-mentioned slurry for the second positive electrode layer is applied to the positive electrode current collector.

[0085] Subsequently, a mixture of the first positive electrode active material and the second positive electrode active material, the aforementioned conductive material, the aforementioned binder, and the solvent are mixed to obtain a slurry for the first positive electrode layer, and the first positive electrode layer slurry is applied onto the slurry for the second positive electrode layer.

[0086] Subsequently, these slurries are dried to form a positive electrode layer on the positive current collector, which sequentially includes a second positive electrode layer and a first positive electrode layer.

[0087] When forming the positive electrode layer, a pressing process can also be performed to press the positive electrode layer in the thickness direction. Examples of pressing processes include roller presses and flat presses.

[0088] Examples of solvents include water, N-methylpyrrolidone (NMP), tetrahydronaphthalene, diisobutyl ketone, butyl butyrate, mesitylene, heptane, dibutyl ether, decane, dodecane, isodecane, and toluene, and may contain two or more of these components.

[0089] Materials used as positive current collectors include, for example, SUS, Cr, Au, Pt, Zn, aluminum, copper, nickel, iron, titanium, and carbon. The thickness of the positive current collector is, for example, 0.1 μm or more and 100 μm or less. The shape of the positive current collector can be foil-like, plate-like, etc. The top view shape of the positive current collector is not particularly limited; for example, circular, elliptical, rectangular, and arbitrary polygonal shapes are possible. The positive current collector can also be a structure with a buffer layer, elastic layer, or PTC (Positive Temperature Coefficient) thermistor layer disposed on its surface.

[0090] [negative electrode]

[0091] The negative electrode has a negative electrode layer and, if necessary, a negative electrode current collector.

[0092] The negative electrode layer is a layer containing at least a negative electrode active material. Additionally, the negative electrode layer may, as needed, contain at least one of an electrolyte, a conductive material, and a binder.

[0093] The negative electrode active material can be in particle or sheet form. The average particle size of the negative electrode active material can be, for example, 1 μm or more. Alternatively, the average particle size of the negative electrode active material can be, for example, 30 μm or less.

[0094] The negative electrode active material may include at least one selected from carbon-based active materials, Li-based active materials, Si-based active materials, Si-C composite materials, and lithium titanate.

[0095] Carbon-based active materials may include at least one selected from graphite, soft carbon, and hard carbon. "Graphite" is a general term for natural graphite and artificial graphite. Graphite can also be a mixture of natural graphite and artificial graphite. The mixing ratio (mass ratio) of natural graphite and artificial graphite may be, for example, "natural graphite / artificial graphite = 1 / 9 to 9 / 1" or "natural graphite / artificial graphite = 3 / 7 to 7 / 3".

[0096] Examples of Li-based active materials include Li, Li silicates, and Li alloys.

[0097] Examples of Si-based active materials include Si, SiO, and Si alloys.

[0098] Si-C composite materials refer to composite materials of carbon-based active materials (such as graphite) and Si-based active materials (such as Si). For example, Si particles may be dispersed within carbon particles. For example, Si particles may be dispersed within graphite particles. For example, Li silicate particles may also be covered by carbon materials (such as amorphous carbon).

[0099] Regarding the electrolyte, conductive material, and adhesive used in the negative electrode layer, the same substances as those described in the positive electrode layer above can be listed.

[0100] The negative electrode layer may also contain a thickener, as needed. Examples of thickeners include carboxymethyl cellulose (CMC).

[0101] Materials used as negative electrode current collectors include, for example, SUS, aluminum, copper, nickel, iron, titanium, and carbon. The thickness of the negative electrode current collector can range from 1 μm to 50 μm. The shape of the negative electrode current collector can be foil-like, plate-like, etc. The top view shape of the negative electrode current collector is not particularly limited; for example, circular, elliptical, rectangular, and arbitrary polygonal shapes are possible. The negative electrode current collector can also have a structure with a buffer layer, elastic layer, or PTC thermistor layer disposed on its surface.

[0102] [Electrolyte layer]

[0103] The electrolyte layer is a layer formed between the positive electrode layer and the negative electrode layer, and it contains at least an electrolyte. The electrolyte can be a solid electrolyte or a liquid electrolyte (electrolyte).

[0104] The electrolyte layer may contain solid electrolytes, electrolyte solutions, etc.

[0105] Solid electrolytes can be listed as the same solid electrolytes described in the above positive electrode layer.

[0106] Electrolytes can be aqueous or non-aqueous. They can be used alone or in combination of two or more.

[0107] Aqueous electrolytes contain water as a main solvent component. That is, based on the total amount of solvent (liquid component) constituting the electrolyte (100 mol%), water can account for 50 mol% or more, particularly 70 mol% or more, and further 90 mol% or more. On the other hand, there is no particular upper limit to the proportion of water in the solvent.

[0108] The solvent contains water as the main component, but may also contain solvents other than water. Examples of solvents other than water include one or more selected from ethers, carbonates, nitriles, alcohols, ketones, amines, amides, sulfur compounds, and hydrocarbons. Based on the total amount of the solvent (liquid component) constituting the electrolyte (100 mol%), the solvents other than water may be 50 mol% or less, particularly 30 mol% or less, and further, 10 mol% or less.

[0109] The aqueous electrolyte used in this disclosure contains an electrolyte. The electrolyte used in the aqueous electrolyte can be any electrolyte known in the past. Examples of electrolytes include lithium salts, nitrates, acetates, and sulfates of imine compounds. Specific examples of electrolytes include lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(pentafluoroethanesulfonyl)imide (LiBETI), lithium bis(nonafluorobutanesulfonyl)imide, lithium nonafluoro-N-[(trifluoromethanesulfonyl)butanesulfonamide], N,N-hexafluoro-1,3-disulfonylimide, CH3COOLi, LiPF6, LiBF4, Li2SO4, and LiNO3.

[0110] The concentration of the electrolyte in an aqueous electrolyte solution can be appropriately set according to the required battery characteristics, within a range that does not exceed the saturation concentration of the electrolyte relative to the solvent. This is because the presence of residual solid electrolyte in the aqueous electrolyte solution may hinder the battery reaction.

[0111] For example, when using LiTFSI as the electrolyte, each kg of water in the aqueous electrolyte may contain more than 1 mol of LiTFSI, particularly more than 5 mol, and further more than 7.5 mol. There is no particular upper limit, for example, it may be less than 25 mol.

[0112] As a non-aqueous electrolyte, an electrolyte containing lithium salt and non-aqueous solvent is usually used.

[0113] Examples of lithium salts include inorganic lithium salts such as LiPF6, LiBF4, LiClO4, and LiAsF6; and organic lithium salts such as LiCF3SO3, LiN(SO2CF3)2 (Li-TFSI), LiN(SO2C2F5)2, and LiC(SO2CF3)3.

[0114] As non-aqueous solvents, examples include ethylene carbonate (EC), propylene carbonate (PC), butyl carbonate (BC), dimethyl carbonate (DMC), diethyl carbonate (DEC), methyl ethyl carbonate (EMC), γ-butyrolactone, sulfolane, acetonitrile (AcN), dimethoxymethane, 1,2-dimethoxyethane (DME), 1,3-dimethoxypropane, diethyl ether, tetraethylene glycol dimethyl ether (TEGDME), tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide (DMSO), and mixtures thereof. From the viewpoint of ensuring high dielectric constant and low viscosity, it can be a mixture of cyclic carbonate compounds such as EC, PC, and BC with high dielectric constant and high viscosity and chain carbonate compounds such as DMC, DEC, and EMC with low dielectric constant and low viscosity, or a mixture of EC and DEC.

[0115] The concentration of lithium salt in non-aqueous electrolytes can be, for example, 0.3~5M.

[0116] Non-aqueous electrolytes can also contain ionic liquids. Ionic liquids can include, for example, salts selected from sulfonium salts, ammonium salts, pyridinium salts, piperidine salts, pyrrolidine salts, morpholine salts, etc. Salt, imidazole At least one of salts and their derivatives.

[0117] The electrolyte layer can also be a membrane that is impregnated with the above-mentioned electrolyte and prevents the positive electrode layer and the negative electrode layer from contacting each other.

[0118] The material used for the membrane is not particularly limited as long as it is a porous membrane. Examples include resins such as polyethylene (PE), polypropylene (PP), polyester, polyvinyl alcohol, cellulose, and polyamide. Polyethylene and polypropylene are also possible materials. Furthermore, the membrane can be a single-layer or multi-layer structure. Examples of multi-layer membranes include two-layer PE / PP membranes, or three-layer PP / PE / PP or PE / PP / PE membranes.

[0119] The diaphragm can also be made of resin nonwoven fabric, glass fiber nonwoven fabric, or other nonwoven fabrics.

[0120] [Solid electrolyte layer]

[0121] The electrolyte layer can be a solid electrolyte layer composed of solids.

[0122] In the case where the electrolyte layer is a solid electrolyte layer, the solid electrolyte layer contains a solid electrolyte and, if necessary, an adhesive, etc.

[0123] The solid electrolyte used in the solid electrolyte layer can be the same substance as that described in the positive electrode layer above.

[0124] Solid electrolytes can be used alone or in combination with two or more types. Furthermore, when using two or more solid electrolytes, they can be mixed, or they can form two or more layers of solid electrolytes to create a multilayer structure.

[0125] The proportion of solid electrolyte in the solid electrolyte layer is not particularly limited. For example, it can be 50% or more by mass, or it can be in the range of 60% or more and 100% by mass, or it can be in the range of 70% or more and 100% by mass, or it can be 100% by mass. The solid electrolyte layer may also contain less than 1% by mass of electrolyte relative to the total amount of solid electrolyte layer.

[0126] Examples of adhesives that can be contained in the above-mentioned positive electrode layer can be cited as examples.

[0127] The content of the binder in the solid electrolyte layer can be 0% by mass to 10% by mass, relative to the total amount of the solid electrolyte layer.

[0128] The thickness of the electrolyte layer can be, for example, 0.1 μm or more and 1000 μm or less, or 0.1 μm or more and 500 μm or less.

[0129] The battery disclosed herein may further include a constraint clamp that applies constraint pressure to the positive electrode layer, the electrolyte layer, and the negative electrode layer along the thickness direction. Particularly when the electrolyte layer is a solid electrolyte layer, constraint pressure may be applied to form good ion conduction pathways and electron conduction pathways. The constraint pressure may be, for example, 0.1 MPa or more, 1 MPa or more, or 5 MPa or more. On the other hand, the constraint pressure may be, for example, 100 MPa or less, 50 MPa or less, or 20 MPa or less.

[0130] [Battery]

[0131] The type of battery disclosed herein is not particularly limited, but a typical example is a lithium-ion battery. Furthermore, the battery disclosed herein can be a liquid battery with an electrolyte layer containing an electrolyte solution, or a solid battery with an electrolyte layer containing a solid electrolyte. A solid battery can be a semi-solid battery or a fully solid battery. In this disclosure, a semi-solid battery is a battery in which the electrolyte layer contains both solid components such as inorganic solid electrolytes and liquid components (e.g., solvents and electrolyte solutions). In this disclosure, a fully solid battery is a battery in which the electrolyte layer contains only solid components such as inorganic solid electrolytes as the electrolyte. Additionally, the battery disclosed herein can be a primary battery or a secondary battery, with a secondary battery being preferred. This is because it can be repeatedly charged and discharged, making it useful, for example, as a vehicle battery.

[0132] There are no particular limitations on the shape of the battery; for example, it can be coin-shaped, cylindrical, square, sheet-shaped, button-shaped, flat, or stacked.

[0133] In the case of a battery stack containing multiple batteries, the battery stack can be either unipolar or bipolar.

[0134] Batteries are used in various applications, including as power sources for vehicles such as hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), battery electric vehicles (BEVs), gasoline vehicles, and diesel vehicles. In particular, they can be used as power sources for driving hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), or battery electric vehicles (BEVs). Furthermore, batteries can be used as power sources for mobile devices other than vehicles (such as trains, ships, and airplanes), and also for electrical appliances such as information processing devices.

[0135] Furthermore, this disclosure is not limited to the embodiments described above. The embodiments described above are illustrative, and any technical solution having a structure that is substantially the same as the technical concept described in the claims of this disclosure and achieving the same effect is included within the technical scope of this disclosure.

[0136] [Example]

[0137] (Example 1)

[0138] [The production of the positive electrode]

[0139] The positive electrode active material is olivine-type LFP (average particle size 1.1 μm) as the first positive electrode active material and olivine-type LMFP (average particle size 0.5 μm) as the second positive electrode active material.

[0140] The composition ratio of Mn to Fe in LMFP, which is the second positive electrode active material, is Mn:Fe = 50:50 moles.

[0141] Using a scraper, the second positive electrode layer, containing the second positive electrode active material, CNTs as conductive material, and polyvinylidene fluoride as binder, is applied to a slurry with a unit area weight of 13 mg / cm². 2 It is coated on an Al foil (30 μm thick) that serves as the positive current collector.

[0142] The composition of the slurry for the second positive electrode layer is: second positive electrode active material: conductive material: binder = 94.5: 1.5: 4.0 by mass ratio.

[0143] Subsequently, a slurry containing a mixed positive electrode active material (comprising a first positive electrode active material and a second positive electrode active material), CNTs as a conductive material, and polyvinylidene fluoride as a binder, was applied using a scraper to achieve a weight of 13 mg / cm². 2 The paste is applied to the second positive electrode layer in a specific manner.

[0144] The proportion of the first positive electrode active material in the mixed positive electrode active material is 20 by mass.

[0145] The composition of the slurry for the first positive electrode layer is a mixture of positive electrode active material, conductive material, and binder in a mass ratio of 94.5:1.5:4.0.

[0146] Subsequently, the cathode was dried at 100°C for 10 minutes to fabricate a cathode having a second cathode layer and a first cathode layer sequentially on the cathode current collector. The cathode layers were fabricated with the same thickness as the first cathode layer. Pressing was performed to achieve a density of 2.3 g / cc for both the second and first cathode layers. The fabricated cathode layers have a structure where the first cathode layer contains LFP while the second cathode layer does not.

[0147] [Making the negative electrode]

[0148] A negative electrode slurry was prepared, comprising artificial graphite (average particle size 22 μm) as the negative electrode active material, SBR as the binder, and CMC as the thickener. The composition of the negative electrode slurry was negative electrode active material:SBR:CMC = 96:3:1 by mass. The negative electrode slurry was prepared by scraping with a doctor blade to a weight of 13 mg / cm³. 2 The cathode was coated onto a Cu foil (15 μm thick) serving as the negative current collector in a manner that resulted in a positive-to-negative capacity ratio of 1.1. Subsequently, it was dried at 100°C for 10 minutes to fabricate a negative electrode with a negative electrode layer on the negative current collector. The electrode was then pressed to achieve a negative electrode layer density of 1.25 g / cc.

[0149] [Battery Manufacturing]

[0150] A battery (laminated cell) was fabricated by stacking the positive electrode, separator (a 3-layer structure of PP / PE / PP, 16 μm thick), and negative electrode. A 1.1 M LiPF6 solution containing LiPF6 as the electrolyte and ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) in a volume ratio of EC:DMC:EMC = 30:40:30 was prepared as the solvent. The battery's confinement pressure was 500 kPa.

[0151] [Activation and Characterization Evaluation]

[0152] The produced units were activated and their properties were evaluated.

[0153] The initial charging current is constant current-constant voltage, with a constant current value of 0.1C to charge to 4.30V, and the constant voltage charging time reaches 3 hours.

[0154] Subsequently, the battery is activated by discharging at a constant current of 0.1C to 3.0V.

[0155] After activation treatment, the charge amount (ΔSOC) was calculated when charging at a constant current of 1C until the cell voltage limit (4.30V) was reached. The results are shown in Table 1. The baseline ΔSOC value of 100% is the charge amount when charging at a current of 0.1C until the cell voltage limit (4.30V) was reached.

[0156] (Example 2)

[0157] In the above-described [fabrication of the positive electrode], the proportion of the first positive electrode active material in the mixed positive electrode active material used in the slurry for the first positive electrode layer was set to 10% by mass. Otherwise, the battery was fabricated in the same manner as in Example 1, and the above-described [activation and characteristic evaluation] was performed. The results are shown in Table 1.

[0158] (Example 3)

[0159] In the above-described [cathode fabrication], LMFP, composed of Mn and Fe in a ratio of Mn:Fe = 60:40 mol%, was used as the second positive electrode active material. Otherwise, the battery was fabricated in the same manner as in Example 1, and the above-described [activation and characteristic evaluation] was performed. The results are shown in Tables 1-2.

[0160] (Example 4)

[0161] In the above-described [cathode fabrication], LMFP, composed of Mn and Fe in a ratio of Mn:Fe = 75:25 mol%, was used as the second positive electrode active material. Otherwise, the battery was fabricated in the same manner as in Example 1, and the above-described [activation and characteristic evaluation] was performed. The results are shown in Table 1.

[0162] (Comparative Example 1)

[0163] Instead of the above-described [fabrication of the positive electrode], a positive electrode with a single-layer structure was fabricated as follows. The battery was then fabricated in the same manner as in Example 1, and the above-described [activation and characteristic evaluation] was performed. The results are shown in Table 1.

[0164] [Fabrication of a positive electrode with a single-layer positive electrode structure]

[0165] The positive electrode active material does not use olivine-type LFP (average particle size 1.1 μm) as the first positive electrode active material, but only olivine-type LMFP (average particle size 0.5 μm) as the second positive electrode active material.

[0166] The composition ratio of Mn to Fe in LMFP, which is the second positive electrode active material, is Mn:Fe = 50:50 moles.

[0167] Using a scraper, a slurry containing the second positive electrode active material, CNTs as conductive materials, and polyvinylidene fluoride as a binder was applied to the positive electrode layer, achieving a weight of 13 mg / cm² per unit area. 2 It is coated on an Al foil (30 μm thick) that serves as the positive current collector.

[0168] The composition of the slurry for the positive electrode layer is: second positive electrode active material: conductive material: binder = 94.5: 1.5: 4.0 by mass ratio.

[0169] Subsequently, the cathode with a positive electrode layer on the positive current collector was fabricated by drying at 100°C for 10 minutes. The positive electrode layer was fabricated with the same thickness as the combined thickness of the second and first positive electrode layers in Example 1. The cathode was then pressed to achieve a density of 2.3 g / cc.

[0170] (Comparative Example 2)

[0171] In the above-described fabrication of a positive electrode with a single-layer structure, olivine-type LFP (average particle size 1.1 μm) was used as the first positive electrode active material, and olivine-type LMFP (average particle size 0.5 μm) was used as the second positive electrode active material. A mixed positive electrode active material of the first and second positive electrode active materials was used as the slurry for the positive electrode layer. The proportion of the first positive electrode active material in the mixed positive electrode active material was set to 10% by mass. Otherwise, the battery was fabricated in the same manner as in Comparative Example 1, and the above-described activation and characteristic evaluation were performed. The results are shown in Table 1.

[0172] (Comparative Example 3)

[0173] In the above-described [Fabrication of a positive electrode with a single-layer positive electrode layer], the proportion of the first positive electrode active material in the mixed positive electrode active material was set to 20% by mass. Otherwise, the battery was fabricated in the same manner as in Comparative Example 2, and the above-described [Activation and Characteristic Evaluation] was performed. The results are shown in Table 1.

[0174] (Comparative Example 4)

[0175] In the above-described fabrication of a positive electrode with a single-layer structure, LMFP, composed of Mn and Fe in a ratio of Mn:Fe = 60:40 mol%, was used as the second positive electrode active material. Otherwise, the battery was fabricated in the same manner as in Comparative Example 1, and the above-described activation and characteristic evaluation were performed. The results are shown in Table 1.

[0176] (Comparative Example 5)

[0177] In the above-described fabrication of a positive electrode with a single-layer structure, LMFP, composed of Mn and Fe in a ratio of Mn:Fe = 60:40 mol%, was used as the second positive electrode active material. Otherwise, the battery was fabricated in the same manner as in Comparative Example 2, and the above-described activation and characteristic evaluation were performed. The results are shown in Tables 1-2.

[0178] (Comparative Example 6)

[0179] In the above-described fabrication of a positive electrode with a single-layer structure, LMFP, composed of Mn and Fe in a ratio of Mn:Fe = 75:25 mol%, was used as the second positive electrode active material. Otherwise, the battery was fabricated in the same manner as in Comparative Example 1, and the above-described activation and characteristic evaluation were performed. The results are shown in Table 1.

[0180] (Comparative Example 7)

[0181] In the above-described fabrication of a positive electrode with a single-layer structure, LMFP, composed of Mn and Fe in a ratio of Mn:Fe = 75:25 mol%, was used as the second positive electrode active material. Otherwise, the battery was fabricated in the same manner as in Comparative Example 2, and the above-described activation and characteristic evaluation were performed. The results are shown in Table 1.

[0182] (Comparative Example 8)

[0183] The battery was fabricated in the same manner as in Comparative Example 5. In the above [Activation and Characteristic Evaluation] section, after activation treatment, the charge amount (ΔSOC) was calculated when the battery was charged at a constant current of 1C until the upper limit of the cell voltage (4.35V) was reached. The results are shown in Table 2.

[0184] (Comparative Example 9)

[0185] The battery was fabricated in the same manner as Comparative Example 5. In the above [Activation and Characteristic Evaluation] section, after activation treatment, the charge amount (ΔSOC) was calculated when the battery was charged at a constant current of 1C until the upper limit of the cell voltage (4.40V) was reached. The results are shown in Table 2.

[0186] (Comparative Example 10)

[0187] The battery was fabricated in the same manner as Comparative Example 5. In the above [Activation and Characteristic Evaluation] section, after activation treatment, the charge amount (ΔSOC) was calculated when the battery was charged at a constant current of 1C until the upper limit of the cell voltage (4.45V) was reached. The results are shown in Table 2.

[0188] (Comparative Example 11)

[0189] The battery was fabricated in the same manner as Comparative Example 5. In the above [Activation and Characteristic Evaluation] section, after activation treatment, the charge amount (ΔSOC) was calculated when the battery was charged at a constant current of 1C until the upper limit of the cell voltage (4.50V) was reached. The results are shown in Table 2.

[0190] Table 1

[0191]

[0192] Table 2

[0193]

[0194] [Comparison of LMFPs using the same Mn ratio]

[0195] The positive electrode layer in Examples 1-4 is a bilayer structure comprising a first positive electrode layer and a second positive electrode layer, wherein the first positive electrode layer contains LFP as the first positive electrode active material.

[0196] Comparing the batteries of Examples 1-2 and Comparative Examples 1-3, which used LMFP with the same Mn ratio as the second positive electrode active material, it can be seen that the batteries of Examples 1-2 have a higher ΔSOC during fast charging at 1C compared to the batteries of Comparative Examples 1-3. Comparing the batteries of Comparative Examples 1-3, it can be seen that increasing the LFP content improves the ΔSOC during fast charging at 1C, but not as much as in Examples 1-2.

[0197] Comparing the batteries of Example 3 and Comparative Examples 5-6, which use LMFP with the same Mn ratio as the second positive electrode active material, it can be seen that the batteries of Example 3 have a higher ΔSOC during fast charging at 1C compared to the batteries of Comparative Examples 5-6.

[0198] Comparing the batteries of Example 4 and Comparative Examples 7-8, which use LMFP with the same Mn ratio as the second positive electrode active material, it can be seen that the batteries of Example 4 have a higher ΔSOC during fast charging at 1C compared to the batteries of Comparative Examples 7-8.

[0199] As can be seen from the above, compared with containing LFP and LMFP in the positive electrode layer of a 1-layer structure, the fast charging performance of the battery is improved when LFP is contained in the first positive electrode layer on the electrolyte layer side as a 2-layer structure.

[0200] [Comparison of different LFP contents in a two-layer cathode structure]

[0201] Comparing the batteries of Examples 1 and 2, it can be seen that the battery of Example 1, which has a higher LFP content as the first positive electrode active material in the first positive electrode layer, has a higher ΔSOC during fast charging at 1C compared to the battery of Example 2.

[0202] [Comparison of LMFPs with different Mn ratios in a two-layer cathode structure]

[0203] Comparing the batteries of Examples 1, 3-4 that use LMFP with different Mn ratios as the second positive electrode active material, it can be seen that the battery of Example 1 has a higher ΔSOC during fast charging at 1C compared with the batteries of Examples 3-4.

[0204] The higher the Mn ratio in LMFP, the lower the fast charging performance of the battery. However, by including LFP in the first positive electrode layer, the fast charging performance of the battery can be improved even when using LMFP with a high Mn ratio.

[0205] [Comparison of different upper voltage limits for batteries]

[0206] Comparing the batteries in Comparative Examples 4, 8-11, increasing the upper limit voltage from 4.30V to 4.50V resulted in a longer time to reach the upper limit voltage, thus improving the battery's fast charging performance. The ΔSOC of the battery in Comparative Example 10, with its upper limit voltage increased to 4.45V, during fast charging at 1C was approximately equal to that of the battery in Example 3. However, increasing the upper limit voltage made the electrolyte more prone to decomposition, increasing gas production and thus shortening the battery's lifespan.

Claims

1. A battery, comprising, in sequence, a positive electrode, an electrolyte layer, and a negative electrode. The positive electrode, starting from the electrolyte layer side, has a positive electrode layer and a positive electrode current collector in sequence. The positive electrode layer contains lithium manganese iron phosphate (LMFP) and lithium iron phosphate (LFP) with an olivine structure as positive electrode active materials. The upper limit voltage of the battery is less than 4.45V. The positive electrode layer is divided into two equal parts in a direction perpendicular to the thickness direction. When the electrolyte layer side is used as the first positive electrode layer and the positive current collector side is used as the second positive electrode layer, the lithium iron phosphate content of the first positive electrode layer is greater than that of the second positive electrode layer.

2. The battery according to claim 1, wherein the proportion of lithium iron phosphate contained in the second positive electrode layer on the positive electrode current collector side is less than 10% by mass relative to the total of lithium manganese iron phosphate and lithium iron phosphate.

3. The battery according to claim 1, wherein the ratio of Mn to the total of Mn and Fe in the lithium manganese iron phosphate, Mn / (Mn+Fe), is 50 mol% or more.

4. The battery according to claim 1, wherein the upper limit voltage of the battery is 4.40V or less.

5. The battery according to claim 1, wherein the proportion of lithium iron phosphate contained in the first positive electrode layer on the electrolyte layer side relative to the total proportion of lithium manganese iron phosphate and lithium iron phosphate is 20% or more by mass.

Citation Information

Patent Citations

  • Pause generator

    JP1986032180A

  • Lithium iron phosphate positive electrode sheet and related secondary batteries, battery modules, battery packs and electrical devices

    JP2024519752A